Fostering Nationalism Character and Insight Nationality in Indonesia-Malaysia Border Students Through a Culture of Local Wisdom - Iwan Ramadhan (Peneliti.net, 2023)
The purpose of this study is to find out how to cultivate the character of nationalism and national insight in Indonesian-Malaysian border students through a culture of local wisdom. The method used in this study is a descriptive qualitative method. The data collection technique carried out in this study was through interviews and documentation. The results of this study are as follows: The culture of local wisdom on the Indonesia-Malaysia border is still well maintained, and the existing nationalism is still well maintained, this is evidenced by them still using goods derived from domestic products, although some products come from abroad. In cultivating a nationalistic character, especially in the Indonesia-Malaysia border area, it is necessary to increase more in cultivating the character of nationalism, that the values of nationalist character include ways of thinking, behaving, and doing that show loyalty, concern, and high appreciation for the language, physical environment, social, cultural, economic, and political of the nation, which upholds and places the interests of the nation and state.